Activist Laboratories of the 1990's. - Wolfson, Todd (Cultural Studies, 2014)
In the 1990s, as the Internet went public, a throng of technological utopianists began declaring the coming of an authentic social, political and democratic revolution. In the reflection of instantaneous, unregulated flows of information and countless self-generating channels of communication, a growing group of pundits saw the promise of an empowered and engaged citizenry that could rewrite the balance of power in society. Breathing life into these quixotic visions, young, white, college-educated men across North America, Europe and Australia flocked to the Internet. These computer programmers-cum-activists took to the Internet with the vision of protecting the non-hierarchical nature of this new communications medium, while harnessing its powers to support a myriad of political organizing projects. In this paper, I look at three of the most critical media activist projects of the 1990s: BURN!, Z Media Institute and CounterMedia and make two interrelated arguments. First is BURN!, then ZMI and CounterMedia, as well as other activist laboratories, were the central sites where the cultural logic and media practices of contemporary social movements began to take shape, particularly as this logic was actualized through technology. Second, I argue that the class position of the new media activists led to a specific understanding of resistance and, correspondingly, the role of technology in social change. Thus, while the activist laboratories of the north created critical new media tools and open, participatory communications platforms, there was a tendency for technology itself to become the answer to social ills.